Divine Meaning Through Science: A Holistic Study of Islamic Integration in Addressing Modern Multidimensional Crises - Muhammad Syauqi Arinal Haq; Suadi Saad; Masykur Wahid (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2026)
This article examines the search for divine meaning in science through a holistic integrative framework grounded in Islamic epistemology, particularly in response to the multidimensional crises characterizing modern society. Contemporary science, while technologically advanced, often operates within a reductionist and value-neutral paradigm that marginalizes ethical and spiritual dimensions. This study aims to analyze how the integration of Islamic spiritual principles can reorient scientific inquiry toward a more meaningful and ethically grounded paradigm. Employing a qualitative library-based research method, the study conducts a critical–descriptive analysis of classical and contemporary scholarly works on science–religion integration, holistic epistemology, and modern civilizational crises. The discussion demonstrates that positioning science within a tauhid-based worldview enables a reconceptualization of natural phenomena as both empirical realities and signs of divine order, thereby restoring ethical orientation, existential meaning, and epistemic coherence in scientific practice. The scholarly contribution of this article lies in its formulation of “divine meaning in science” as a conceptual epistemological framework that bridges empirical inquiry with spiritual consciousness, rather than merely advocating methodological dialogue between science and religion. This approach provides a specific conceptual alternative for addressing ecological, moral, and existential crises by repositioning science as a value-oriented and integrative human endeavor.